Together, the IFT81 and IFT74 N-termini form the main module for intraflagellar transport of tubulin - Kubo, Tomohiro (J Cell Sci, 2016)
The assembly and maintenance of most cilia and flagella rely on intraflagellar transport (IFT). Recent in vitro studies have suggested that, together, the calponin-homology domain within the IFT81 N-terminus and the highly basic N-terminus of IFT74 form a module for IFT of tubulin. By using Chlamydomonas mutants for IFT81 and IFT74, we tested this hypothesis in vivo. Modification of the predicted tubulin-binding residues in IFT81 did not significantly affect basic anterograde IFT and length of steady-state flagella but slowed down flagellar regeneration, a phenotype similar to that seen in a strain that lacks the IFT74 N-terminus. In both mutants, the frequency of tubulin transport by IFT was greatly reduced. A double mutant that combined the modifications to IFT81 and IFT74 was able to form only very short flagella. These results indicate that, together, the IFT81 and IFT74 N-termini are crucial for flagellar assembly, and are likely to function as the main module for IFT of tubulin.